RELATIONSHIP BETWEEN GENOTYPES OF THE HEAT SHOCK GENE HSP90, CONCENTRATIONS OF SOME BIOCHEMICAL AND ELEMENTS BLOOD PARAMETERS OF HOLSTEIN FRIESIAN COWS - Marwa Hussein Razaq Al-Mousawi, Walid Yousef Qassim and Mohammed Abdul-Wahab Ati, (Chelonian Research Foundation, 2023)
The experiment was conducted at Taj Al-Nahrain Research Station, north of Diwaniyah Governorate, by using 35 Holstein cows for the period between 1/3/2022 to 15/8/2022, to demonstrate the effect of the relationship between genetic polymorphisms of the heat shock gene HSP90, and some biochemical characteristics of Holstein Friesian cows. These cows were divided into three seasons as follows: the first season (11 cows), the second season (15 cows), and the third season (9 cows), based on station records. The cows were placed in semi-shaded pens with a length of 140 m and a width of 60 m for each pen, these pens were provided with freely filled water basins, after that, the genetic part was analyzed in the Molecular Genetics Laboratory of the College of Agriculture, University of Basrah. The remainder of the genetics results (Skonsk) were completed at BIONEER Laboratories Company in Seoul/Korea. As for the physiological traits, they were analyzed in the Physiology Laboratory of the College of Agriculture, University of Basrah. The results show that a significant increase of the CT and TT genotypes compared to the CC genotype on the potassium concentration in the blood of Holstein cows, with a significant increase of the CT genotype compared to the TT genotype in the concentration of urea in blood serum, there were no significant differences between all genotypes on the concentration of glucose, cholesterol, triglycerides, albumin, total protein, phosphorus, and calcium. Keywords: heat shock gene HSP90, biochemical, elements, blood parameters, Holstein Friesian cows.